The Role of Daily Routines in Fostering Independence among Children Aged 4–5 Years - Fajri Rahmi; Nurasiah Ahmad; Hilma Nafsiyati; Rana Nabilah; Irawati Irawati (STIT Ahlussunnah Bukittinggi, 2026)
Independence is an essential aspect of early childhood development as it supports children's ability to regulate themselves, make simple decisions, and take responsibility for their surroundings. This study aims to analyze the role of daily routines in fostering independence among children aged 4–5 years in a kindergarten setting. The study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving children aged 4–5 years, classroom teachers, and the school principal. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation. The findings revealed that consistently implemented daily routines provided opportunities for children to develop various aspects of independence, including active participation in school activities, the ability to complete tasks without assistance, responsibility for using and organizing learning materials, independence during mealtimes, and emotional self-management. Routine activities such as lining up, praying together, washing hands, eating together, and tidying up learning materials served as effective habituation practices in fostering independent behavior. The findings highlight that daily routines play an important role in supporting the development of independence in early childhood, with consistent habituation and teacher guidance serving as key factors in their effectiveness. This study suggests that integrating daily routines into learning activities can be an effective strategy for strengthening children's independence in early childhood education settings.